Upaya Meningkatkan Persatuan Keberagaman Agama - Reyin, Anis Sunnai; Albina, Meyniar (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Indonesia is a country rich in religious, cultural, and ethnic diversity. However, this diversity often presents challenges in maintaining unity. This study aims to identify strategic efforts that can be made to improve unity amidst religious diversity. The method used is a literature review. The results of the study indicate that interfaith dialogue, early tolerance education, strengthening the role of religious institutions, and campaigns through social media are effective steps in strengthening unity. In addition, collaboration in cross-religious social activities has also been proven to be able to build harmonious relationships. Thus, a joint commitment is needed from all elements of society and government to continue to encourage the creation of strong harmony amidst the nation's plurality.